Design and Development of an Online Game - Norhayati Yusoff; Marzita Puteh; Azman Mokhtar; Sukor Beram; Norzalina Noor; Abdul Halim Ismail; Wong Wei Lun (Malaysia Journal of Invention and Innovation, 2023)
In general, classroom teaching and learning approaches place less emphasis on students’ comprehension and more on the results of activities that do not promote students’ thinking. Educators have begun to employ technology in the classroom and online as a teaching aid. This study employs a research methodology based on design and development research (DDR). The procedure consisted of three steps. The first step consisted of a needs analysis by delivering questionnaires to 500 Form Two students. The design and application development phase is the second step. It requires expert consensus on application components (constructs and items) utilising the Fuzzy Delphi Method (FDM). Eleven panels of subject matter experts utilised the FDM technique to authenticate the application’s content. The study’s third step is the evaluation phase. The quasi-experiment was conducted with a total of sixty students in Form Two. The first phase’s findings indicated a requirement for constructing an application with a mean value of 3.382% for the perception of Form Two students’ interest in online games. The second phase of the research, based on the consensus of experts, has yielded seven primary constructs and 39 elements for this application. The final phase of the trial revealed that Form Two students in the treatment group performed better than those in the control group. In turn, this could boost student interest; nevertheless, because the hypotheses were accepted, there was no significant correlation between interest and achievement in the treatment group. In conclusion, the researcher proposed that the application may be used more broadly and contribute to mathematics teaching. The consequences of the study indicate that the Ministry of Education and schools can use this application to develop applications for other topics. MathGPro is an upgraded version of MaProsil, with the game in this application being updated to include more questions and levels.